2002
DOI: 10.1016/s1090-5138(01)00090-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adaptation to human sperm competition

Abstract: Sperm competition occurs when the sperm of two or more males simultaneously occupy the reproductive tract of a female and compete to fertilize an egg. We used a questionnaire to investigate psychological responses to the risk of sperm competition for 194 men in committed, sexual relationships in the United States and in Germany. As predicted, a man who spends a greater (relative to a man who spends a lesser) proportion of time apart from his partner since the couple's last copulation reported (a) that his part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 39 publications
4
78
0
Order By: Relevance
“…The results of the current research are consistent with the results of previous research investigating adaptation to sperm competition in humans, notably Shackelford et al (2002) and Gallup et al (2003). Gallup and his colleagues, for example, predicted and documented relationships between a man's suspicions of his partner's sexual infidelities, physical separation from his partner, and a man's copulatory behaviors upon physical reunion with his partner (e.g., engaging in deeper copulatory thrusting following physical separation).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of the current research are consistent with the results of previous research investigating adaptation to sperm competition in humans, notably Shackelford et al (2002) and Gallup et al (2003). Gallup and his colleagues, for example, predicted and documented relationships between a man's suspicions of his partner's sexual infidelities, physical separation from his partner, and a man's copulatory behaviors upon physical reunion with his partner (e.g., engaging in deeper copulatory thrusting following physical separation).…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of time the couple had spent apart since their last copulation was calculated by subtracting the number of hours that the couple had spent together since their last copulation from the total number of hours since the couple's last copulation and dividing this difference by the total number of hours since the couple's last copulation (following Shackelford et al, 2002; also following Baker & Bellis, 1989, 1993, 1995Starratt et al, in press) Shackelford et al, 2002). Distress following partner's denial of a request for copulation (␣ ϭ .89) is the mean of responses to three items: (a) anger following his partner's denial of his request for copulation, (b) frustration following his partner's denial of his request for copulation, and (c) upset feelings following his partner's denial of his request for copulation (following Shackelford et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inseminating more sperm following a separation may function to outnumber or "flush out" rival sperm in the female reproductive tract (Baker & Bellis, 1995;Parker, 1970). Reasoning that there must be psychological adaptations accompanying these physiological adaptations, Shackelford et al (2002) demonstrated that men who spent a greater (relative to men who spent a lesser) proportion of time apart from their partner since the couple's last copulation rated their partners to be more physically attractive and showed greater interest in copulating with their partners. Such psychological adjustments may motivate men to copulate with their partners as soon as possible, placing their sperm in competition with rival sperm that may be present.…”
Section: Sperm Competition and Men's Short-term Matingmentioning
confidence: 99%